2017
DOI: 10.1049/iet-nbt.2017.0064
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of the Maxwell–Wagner and the Bruggeman–Hanai mixture models for single cell dielectric spectroscopy

Abstract: Dielectric spectroscopy (DS) is a non-invasive, label-free, and promising technique for measuring dielectric properties of biological cells. Recent developments in microfabrication techniques made it possible to perform DS measurements with minute volume of cell suspensions. However, when the cell size approaches the size of the measurement chamber, especially, for single cell measurements, the analytical models [Maxwell-Wagner and Bruggeman-Hanai (BH) mixture models] to extract cell parameters lose their accu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 43 publications
(56 reference statements)
0
19
0
Order By: Relevance
“…In order to assess the dielectric spectroscopy response, the impedance spectra of Jurkat cells are analytically generated for planar and rough surfaces using previously published cell data . The Jurkat cells are modeled using the double shell model, which depicts the cells as perfectly spherical particles surrounded by cell membrane and contain cytoplasm and a spherical nucleus separated by a nuclear envelope.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In order to assess the dielectric spectroscopy response, the impedance spectra of Jurkat cells are analytically generated for planar and rough surfaces using previously published cell data . The Jurkat cells are modeled using the double shell model, which depicts the cells as perfectly spherical particles surrounded by cell membrane and contain cytoplasm and a spherical nucleus separated by a nuclear envelope.…”
Section: Resultsmentioning
confidence: 99%
“…An inverse model based on Maxwell‐Wagner and double shell model was used to extract sub‐cellular properties for both cases. The computational flow chart used for the inverse model was given in our previous study . For both cases, medium, cytoplasm, and nucleoplasm permittivity values were fixed at 80, 60, and 120, respectively and medium conductivity was fixed at 1.5 S/m.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The latter is implemented in the software MyDEP 59 with the full methodology explained in the supplementary material of that article and in 10,60 . For higher volume fractions, the Hanai formulation has proven to be more accurate than the Maxwell-Garnett formulation 61 . However, variation of the vertical position of the particle has shown that both models exhibit significant errors when the particle is in close vicinity to the electrodes.…”
Section: Cell Suspensionmentioning
confidence: 99%
“…Confidence in the obtained results depends on the tolerance set for the solving as well as the validation of the mesh used through a mesh convergence study 37 . Error calculation can also be used for adaptive mesh refinement in which the error estimate is used to refine the areas in the volume where the error is the largest 61,78 .…”
Section: Conclusion On Theory and Modelingmentioning
confidence: 99%